Total proximal ureter substitution using buccal mucosa - Fahmy, Omar; Schubert, Tina; Khairul‐Asri, Mohd Ghani; Stenzl, Arnulf; Gakis, Georgios (Wiley, 2017)
The surgical treatment of a long proximal ureteral stricture is a challenging situation for reconstructive surgeons. Despite the underlying morbidities, ileal interposition and autotransplantation are the options available to treat complex cases of long segment ureteral stricture. Buccal mucosa has shown excellent results in urethroplasty. However, its use in ureteral reconstruction is infrequent. We report on a 64‐year‐old female patient with multiple comorbidities and prior abdominal surgeries for Crohn's disease who underwent a successful total substitution of a long segment of the proximal ureter using buccal mucosa. Regular postoperative isotope scans showed improvement in renal function. Based on the pleasant outcome of this case and review of the literature, buccal mucosa might be a viable option with low morbidity in selected cases.